Associations of Forest Cover, Fragment Area, and Connectivity with Neotropical Understory Bird Species Richness and Abundance - Martensen, Alexandre Camargo; Ribeiro, Milton Cezar [UNESP]; Banks-Leite, Cristina; Prado, Paulo Inacio; Metzger, Jean Paul (Wiley-Blackwell, 2012)
Theoretical and empirical studies demonstrate that the total amount of forest and the size and connectivity of fragments have nonlinear effects on species survival. We tested how habitat amount and configuration affect understory bird species richness and abundance. We used mist nets (almost 34,000 net hours) to sample birds in 53 Atlantic Forest fragments in southeastern Brazil. Fragments were distributed among 3 10,800-ha landscapes. The remaining forest in these landscapes was below (10% forest cover), similar to (30%), and above (50%) the theoretical fragmentation threshold (approximately 30%) below which the effects of fragmentation should be intensified. Species-richness estimates were significantly higher (F = 3715, p = 0.00) where 50% of the forest remained, which suggests a species occurrence threshold of 30-50% forest, which is higher than usually occurs (<30%). Relations between forest cover and species richness differed depending on species sensitivity to forest conversion and fragmentation. For less sensitive species, species richness decreased as forest cover increased, whereas for highly sensitive species the opposite occurred. For sensitive species, species richness and the amount of forest cover were positively related, particularly when forest cover was 30-50%. Fragment size and connectivity were related to species richness and abundance in all landscapes, not just below the 30% threshold. Where 10% of the forest remained, fragment size was more related to species richness and abundance than connectivity. However, the relation between connectivity and species richness and abundance was stronger where 30% of the landscape was forested. Where 50% of the landscape was forested, fragment size and connectivity were both related to species richness and abundance. Our results demonstrated a rapid loss of species at relatively high levels of forest cover (30-50%). Highly sensitive species were 3-4 times more common above the 30-50% threshold than below it; however, our results do not support a unique fragmentation threshold.
Keywords: Atlantic Forest; corridors; fragmentation; fragment size; thresholds; tropical landscapes